Contextual analysis of the role of the healthcare-associated infections controller - Matias, Karolayne Cabral (2025)
This study aims to critically analyze the contextual aspects of the role of the Healthcare-Associated Infections (HAIs) Controller. It is a contextual analysis of the role of the HAI Controller, based on the perspective of Hinds, Chaves, and Cypress, and operationalized through a scoping review. The search resulted in a final sample of 58 studies. The following contextual levels were identified: metacontext (standards, resolutions, laws, and global, international, and national public policies related to the theme); general context (responsibilities of HAI Control); specific context (strengths and challenges of HAI Control); and immediate context (the role of the HAI Controller and their specific actions). Identifying the interactive levels of context enabled a comprehensive reflection on how the role of HAI controllers is directed toward reducing preventable infections through prevention and control measures, addressing various aspects of both the environment and safe practices, ultimately improving the quality of patient care.